Accuracy of Cricothyroid Membrane Identification Using Ultrasound and Palpation Techniques in Obese Obstetric Patients: An Observational Study. Issue 3 (24th September 2022) - Lavelle, A.; Drew, T.; Fennessy, P.; McCaul, C.; Shannon, J.
Abstract : ( Int J Obstet Anesth . 2021;48:103205) Emergency front of neck access (e-FONA) is a potentially life-saving intervention but requires the accurate identification of the cricothyroid membrane (CTM). CTM identification failure is most common in obese females, who also have an increased risk of emergency and elective cesarean delivery. This study aimed to compare accuracy of CTM identification using ultrasound (US) compared with palpation in obese obstetric patients.